(untitled) (Ibrahim Cardiac Medical Journal, 2026)
Eosinophilic Esophagitis (EoE) is an increasing cause of upper gastrointestinal morbidity, traditionally reported to be more prevalent in males and atopic populations. Data regarding EoE presentation in adolescent girls from Bangladesh is scarce. We report the case of a 15-year-old Bangladeshi girl who presented with a one-year history of persistent mild daily heartburn, dyspepsia, intermittent solid food dysphagia, and associated weight loss (4.7 kg). Initial upper endoscopic examination and manometric findings were unremarkable. The diagnosis of EoE was definitively confirmed by the histologic examination of biopsy specimens taken from the lower and mid esophagus, which demonstrated marked eosinophilic infiltration consistent with the disease. Treatment commenced with a combination of topical steroids (Fluticasone Propionate + Formoterol Fumarate) and elimination of known allergic diets, resulting in significant improvement in appetite and resolution of dysphagia. This case emphasizes the need for high clinical suspicion among gastroenterologists for EoE in adolescent girls with persistent, non-specific symptoms such as heartburn and dysphagia, and underscores the necessity of performing multiple endoscopic biopsies from both proximal and distal segments to secure a conclusive diagnosis, even in the absence of visual endoscopic abnormalities. Ibrahim Card Med J 2024; 14 (2): 60-63